2019
DOI: 10.3390/biom9050164
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Antihypertensive Peptides from Whey Proteins and Their Releasing in Gastrointestinal Conditions

Abstract: Antihypertensive peptide fraction from whey protein hydrolysate <3 kDa (measured as angiotensin-converting enzyme (ACE) activity %) was isolated and encapsulated into three composite materials: alginate–collagen, alginate Arabic gum, and alginate–gelatin. The release behavior of peptide fraction from capsules was analyzed according to the encapsulation material efficiency, the characteristics of the capsules, and the released antihypertensive peptides during gastrointestinal digestion. The highest encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…The rationale of using «Protamex» in the preparation of hydrolysates from whey proteins with a high degree of hydrolysis is confirmed by the results of [RU 2012158005, Method of producing whey protein hydrolysate with high degree of hydrolysis and low residual antigenicity] and from SPI is shown in [RU 2299568C2 Method for the production of processed cheese, 48]. The effectiveness of the strain of Bacillus subtilis ("Bioprotease N100L") on the depth of hydrolysis of WPC was confirmed in studies [49,50].…”
Section: Dependence Of Hydrolysis Degree Of Isp and Wpc From Timementioning
confidence: 82%
“…The rationale of using «Protamex» in the preparation of hydrolysates from whey proteins with a high degree of hydrolysis is confirmed by the results of [RU 2012158005, Method of producing whey protein hydrolysate with high degree of hydrolysis and low residual antigenicity] and from SPI is shown in [RU 2299568C2 Method for the production of processed cheese, 48]. The effectiveness of the strain of Bacillus subtilis ("Bioprotease N100L") on the depth of hydrolysis of WPC was confirmed in studies [49,50].…”
Section: Dependence Of Hydrolysis Degree Of Isp and Wpc From Timementioning
confidence: 82%
“…To overcome these effects, bioactive peptides or protein hydrolysates can be treated with stabilizing carriers. Several studies suggested that encapsulation of antimicrobial [ 151 ] and antihypertensive peptides [ 152 , 153 ] in liposomes has been suggested to overcome the problems related to the direct application of the peptides in food, as it can keep the structural integrity and functionality of peptides in food matrices [ 154 , 155 ].…”
Section: Application Of Bioactive Peptides In Food Technology and Food Biosafetymentioning
confidence: 99%
“…Lately, studies have reported that enzymatic hydrolysis of cheese whey proteins results in different biomolecules with antioxidant properties [260], anticancer [261], and even opioid functions [251]. Alvarado et al [242] studied the production of antihypertensive peptides from whey protein hydrolysate (<3 kDa) and encapsulated them in order to evaluate angiotensin-converting enzyme activity (ACE%) during GIT digestion [242]. The results revealed about a 10% increase of ACE activity by the released peptides.…”
Section: Whey Proteins: Research Insights and Trendsmentioning
confidence: 99%